Uji Kualitas Sabun Padat Transparan Dari Minyak Kelapa Dan Minyak Kelapa Sawit Dengan Antioksidan Ekstrak Likopen Buah Tomat - Zainal Fanani; Almunady T. Panagan; Novita Apriyani (Faculty of Mathtmatics and Natural Sciences, 2020)
Increasing population growth causes demand for daily necessities to increase as well, one of which is soap, because almost all humans use soap to wash and clean themselves. The purpose of this reseacrh was to determine the optimum ratio of coconut oil and palm oil to produce the best transparent solid soap and tomato lycopene extract added to maximize the benefits of the soap. Characterization includes water content, total fat, insoluble material in ethanol, free alkali, free fatty acids, non-soaped fats, pH, foam stability, and antioxidant activity from lycopene. The best result was soap with ratio of coconut oil and palm oil 1: 0. The resulting soap has a high transparency, smooth foam, water content of 3.546%, foam stability of 96%, and pH of 10. Soap accordance with SNI3532-2016, except the unsaponifiables fat. The analysis results obtained water content of 3.486%, total fat of 73.616%, insoluble material in ethanol of 1.2%, free fatty acid of 0.564%, negative free alkali, unsaponifiables fat of 0.7294% and Lycopene antioxidant activity of 54.85 µg/mL.